PENAMAAN AYAT AL QUR’AN SUATU DISKURSUS PENGEMBANGAN ILMU AL QUR’AN DAN TAFSIR (IAT) - Musyaffa Ahmad Rahim; Amirotun Nafisah (Al Kareem Jurnal Ilmu Al Qur'an dan Tafsir, 2023)
This research aims to find the arguments used by a researcher in the field of the Al-Qur'an and Tafsir in naming one or a group of particular verses, besides that it aims to provide an overview of the open space for researchers in this field. Al-Qur'an and Tafsir use ijtihad in naming one or several verses. The study method follows the inductive method by tracing various references and sources of sharia sciences from the Al-Qur'an and the hadiths of the Prophet Muhammad SAW, as well as a search for classical commentary literature, and other references. This research concludes that the arguments and examples of giving "Verse Names" are found in several verses of the Qur'an whose names were given by the Prophet ?, some were given by the Prophet's companions. (early followers), mufassir (commentators), as well as researchers and scholars. The ijtihad space for naming verses is very open, in contrast to "Names of Surahs" which refers to the principle of tauqifi and "Names of the Qur'an" which do not open up ijtihad spaces.